CAN AUDIT COMMITTEE REDUCE REAL EARNINGS MANAGEMENT? - YULIUS KURNIA SUSANTO; ARYA PRADIPTA (Jurnal Bisnis dan Akuntansi, 2020)
The objective of research was to give empirial evidence the influence of audit committee and directors on real earnings management (REM). The samples of this research consist of 336 data from 84 public manufacturing companies from 2013 until 2016 and selected by purposive sampling method. The result showed that the audit committee expertise and independence directors have significantly and postive influence on REM. The board of directors have significantly and negative influence on REM. The influence of audit committee tenure, size, meeting on REM is not significantly. The results of this reasearch shows that outsider of the firm like audit committee and independence directors can’t detect REM. The chance for management doing REM. While, board of directors as insider of the firm can detect and reduce REM.